MdBBX21, a B-Box Protein, Positively Regulates Light-Induced Anthocyanin Accumulation in Apple Peel - Zhang, Bo; Zhu, Zhen-Zhen; Qu, Dong; Wang, Bo-Chen; Hao, Ni-Ni; Yang, Ya-Zhou; Yang, Hui-Juan; Zhao, Zheng-Yang (Frontiers in Plant Science, 2021)
The red coloration of apple (Malus × domestica Borkh.) is due to the accumulation of anthocyanins in the fruit peel. Light is essential for anthocyanin biosynthesis in apple. In this study, we performed a transcriptome sequencing (RNA-seq) analysis of apple fruit exposed to light after unbagging. The identified differentially expressed genes included MdBBX21, which is homologous to Arabidopsis BBX21, suggesting it may be involved in light-induced anthocyanin biosynthesis. Additionally, MdBBX21 was localized in the nucleus and its gene was expressed earlier than MdMYB1 in apple peel treated with light. Overexpressing MdBBX21 in Arabidopsis and apple calli under light increased anthocyanin accumulation. Dual-luciferase and yeast one-hybrid assays confirmed that MdBBX21 binds to the MdHY5, MdBBX20, and MdBBX22-1/2 promoters and induces expression. Furthermore, bimolecular fluorescence complementation and yeast two-hybrid assays demonstrated that MdBBX21 can interact with MdHY5. This interaction can significantly enhance MdMYB1 promoter activity. These findings clarify the molecular mechanism by which MdBBX21 positively regulates light-induced anthocyanin accumulation in apple.